Lessons from the Heart of Soweto Study and future directions - Pretorius, Sandra; Stewart, Simon; Sliwa, Karen (SA Heart Journal, 2017)
South Africa is concurrently experiencing epidemiological transition with diseases of lifestyle on the increase, while still burdened by poverty related diseases. Chronic diseases of lifestyle such as CVD are rapidly becoming major causes of death in developing countries and by all predictions, will continue rising.(4,7,8,9) Of concern is the fact that in developing countries, CVD is occurring in younger individuals than in the developed countries and as the epidemic evolves, the poor are affected the most in both developed and developing countries.(1) The Heart of Soweto (HOS) study aimed to investigate and describe this emerging problem of CVD, and especially heart disease, amongst the urban African population in Soweto, who presented for the first time to a tertiary-care centre. Overall we found multiple challenges to the community of Soweto and surrounding regions from a combination of high levels of modifiable CV risk factors (with the exception of lipid disorders) and surprisingly high levels of advanced and deadly forms of heart disease affecting predominantly younger cases and women. Lessons learned from the HOS include, (1) building partnerships, (2) establish clear objectives with achievable goals, (3) think big and assume nothing, (4) provide an enabling environment, (5) be innovative and (6) never compromise on quality. The prevention of CVD other chronic diseases of lifestyle, as well as the management thereof, needs to be a multidisciplinary effort with all the necessary healthcare workers involved, implemented at the primary, as well secondary level. Our goal is the development of specific community based intervention programmes directed towards prevention and management of chronic diseases of lifestyle in Soweto and to document the aetiology, presentation and management thereof. Our data collection will be not only meaningful for the population in Soweto, but also in other areas of South Africa and the broader Africa. It will be indicative of any urban African population in transition.